Technical analysis of typical intelligent game system and development prospect of intelligent command and control system - Xiangang LI; Qiang LI (智能科学与技术学报)
In the future era of intelligence,the massive and heterogeneous battlefield data and the widespread use of unmanned platforms will accelerate the expansion of the combat space from the physical and information domains to the cognitive domains,which will put forward higher requirements for the accuracy,timeliness and effectiveness of command and control,and the intelligence of command and control will become the general trend.Based on the analysis of typical foreign intelligent command and control system,the machine game technology development course was clarified,the challenge of applying machine game technology to intelligent command and control system was analyzed,the future intelligent command and control in combat training,operational innovation and prospective of system architecture and implementation was put forward,so as to provide reference and enlightenment for the future development of command and control system.